2019
DOI: 10.1155/2019/7634528
|View full text |Cite
|
Sign up to set email alerts
|

The Attributable Direct Medical Cost of Healthcare Associated Infection Caused by Multidrug Resistance Organisms in 68 Hospitals of China

Abstract: Healthcare associated infection (HAI) is known to increase the economic burden of patients while the medical cost due to MDRO HAI is even higher. Three hundred eighty-one multidrug resistance organisms (MDROs) healthcare associated infection (HAI) case-patients and three hundred eighty-one matched control-patients were identified between January and December in 2015. The average total hospitalization medical cost of the case group was $6127.65 and that of the control group was $2274.02. The difference between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…However, there is no doubt that the indiscriminate use of wide-spectrum antibiotics has been accepted as a definitive risk factor for the emergence of MDR pathogens [21], which have been reported to potentially worsen the severity of UTIs compared with pathogens without the resistance [24]. In other words, MDR would contribute to the high economic burden to the healthcare system due to frequent laboratory examinations, longer length of hospital stay, and administration of broad-spectrum antibiotics for worse infections [25]. A multinational observational study including 20 hospitals in eight countries showed that the presence of MDR was related to a higher cost [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no doubt that the indiscriminate use of wide-spectrum antibiotics has been accepted as a definitive risk factor for the emergence of MDR pathogens [21], which have been reported to potentially worsen the severity of UTIs compared with pathogens without the resistance [24]. In other words, MDR would contribute to the high economic burden to the healthcare system due to frequent laboratory examinations, longer length of hospital stay, and administration of broad-spectrum antibiotics for worse infections [25]. A multinational observational study including 20 hospitals in eight countries showed that the presence of MDR was related to a higher cost [26].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the threat of antibiotic resistance is increasing globally, and this has caused many infectious diseases to become untreatable, with considerable increases in treatment complexity, side effects, disability, and mortality [1,2]. Moreover, it is well established that antibiotic-resistant infectious diseases lead to an increase of healthcare costs for hospitalizations, additional diagnostic investigations, and treatments [3][4][5][6]. The prevention of antibiotic-resistant bacteria's development and diffusion is a worldwide public health priority and requires a complex approach that includes the participation of healthcare professionals, patients, the agricultural sector, and policy makers.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no doubt that the indiscriminate use of widespectrum antibiotics has been accepted as a definitive risk factor for emergence of MDR pathogens, 21 which have been reported to potentially worsen the severity of UTIs compared with pathogens without the resistance [24]. In other words, MDR would contribute to the high economic burden to the healthcare system due to frequent laboratory examinations, longer length of hospital stay, and administration of broad-spectrum antibiotics for worse infections [25]. A multinational observational study including 20 hospitals in eight countries showed that the presence of MDR was related to a higher cost [26].…”
Section: Resultsmentioning
confidence: 99%